1997
DOI: 10.1085/jgp.110.3.257
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Gating of a Large Conductance Ca-activated K+ Channel

Abstract: Large-conductance Ca-activated potassium channels (BK channels) are uniquely sensitive to both membrane potential and intracellular Ca2+. Recent work has demonstrated that in the gating of these channels there are voltage-sensitive steps that are separate from Ca2+ binding steps. Based on this result and the macroscopic steady state and kinetic properties of the cloned BK channel mslo, we have recently proposed a general kinetic scheme to describe the interaction between voltage and Ca2+ in the gating of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
407
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(439 citation statements)
references
References 79 publications
29
407
3
Order By: Relevance
“…All four subunits must be activated before the channel opens. Although speculative, the kinetic diagram is similar to previous proposals for a variety of K Ca channels based upon single-channel data (43)(44)(45). These schemes predict that the steep Hill coefficient determined in functional measurements of the Ca 2ϩ sensitivity of channel opening arises from the requirement for Ca 2ϩ -induced conformational changes by each of four subunits in BK Ca , SK Ca , and, as proposed here, IK Ca channels.…”
Section: Discussionsupporting
confidence: 80%
“…All four subunits must be activated before the channel opens. Although speculative, the kinetic diagram is similar to previous proposals for a variety of K Ca channels based upon single-channel data (43)(44)(45). These schemes predict that the steep Hill coefficient determined in functional measurements of the Ca 2ϩ sensitivity of channel opening arises from the requirement for Ca 2ϩ -induced conformational changes by each of four subunits in BK Ca , SK Ca , and, as proposed here, IK Ca channels.…”
Section: Discussionsupporting
confidence: 80%
“…Such information could place constraints on which types of gating mechanisms are consistent with the observed cooperativity and indicate at which steps in the activation process the cooperative interactions occur. Considerable insight into the mechanism of cooperativity has been obtained by detailed kinetic analysis, which has suggested that the activation of BK channels by Ca 2ϩ and by voltage occurs through separate allosteric mechanisms that modulate the channel opening-closing transitions independently of one another (10,17,18,(20)(21)(22)(23)(24)(25). However, because the gating of BK channels is so complex, it has been necessary in these studies to either make simplifying assumptions about the particular types of the cooperative interactions (10,17,18,(20)(21)(22)25) or to analyze simplified models with fewer assumptions (7,23,24).…”
mentioning
confidence: 99%
“…Currents recorded in 10 and 100 M Ca 2ϩ did not have leak subtraction performed. Typically, at each Ca 2ϩ concentration, two to three families of current traces were recorded consecutively and averaged before analysis (21). All experiments were carried out at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The levels of free Ca 2ϩ in the other solutions were confirmed using a calcium electrode (Orion model 93-20, WPI, Sarasota, FL). 50 M of the divalent cation chelator (ϩ)-18-crown-6-tetracarboxylic acid was present in the bath solution to prevent divalent cation block at high voltages (21,22). The recording chamber (ϳ0.3-ml volume) was perfused at a constant rate of ϳ1 ml/min using a ValveLink TM 16 solenoid bank (AutoMate Scientific, Inc., NY) to switch between various solutions.…”
Section: Methodsmentioning
confidence: 99%